Structural Change in Japan : Macroeconomic Impact and Policy Challenges - Bayoumi, Tamim (International Monetary Fund, 1998)
This volume, by Bijan B. Aghevli, Tamim Bayoumi, and Guy Meredith, is based on a seminar on structural change in Japan held in early 1997 and chaired by the IMF's First Deputy Managing Director, Stanley Fischer. Discussion of teh day-to-day management of the standard levers of fiscal and monetary policy is interlinked with consideration for the more deep-seated structural issues. By shifting and destabilizing the underlying economic relationships and creating uncertainty, structural change complicates the task of policy analysis. This volume describes how the IMF is responding to these challenges and how outside experts assess this effect.